China Spillovers : New Evidence From Time-Varying Estimates - Furceri, Davide; Jalles, Joao Tovar; Zdzienicka, Aleksandra (Washington, D.C. : International Monetary Fund, 2016)
Until recently, China has been the leading contributor to global economic growth and-since the recent global financial crisis-a stabilizing driver of its evolution. However, as China recently began to rebalance its economy away from investment and exports and toward consumption, its GDP growth slowed significantly-partly reversing the country's contribution to global output and trade growth-and is expected to continue to decline gradually over the medium term. There is little consensus regarding the consequences of a China's growth slowdown for the rest of the world, with some arguing that a significant slowdown in China may have large implications and possibly lead to a worldwide recession if the 'rebalancing' process is not well managed, and others suggesting that even a significant slowdown in China is unlikely to have large global effects, as its role in the world economy is still limited This note contributes to the ongoing debate by analyzing how growth shocks in China affect particular regions and country groups and how the impact and key transmission channels of these growth shocks have increased over time. It finds that historically, the average impact of growth shocks in China on global output has been statistically significant but limited, but since the early 2000s, the magnitude of spillovers has significantly increased. Trade linkages remain the main transmission channels, with larger effects for net commodity exporters and countries mostly exporting manufacturing goods. Also, spillover effects tend to be larger during periods of high global uncertainty and have been positively associated with an increase in the share of industry in total value in China, which suggests an important role of the 'rebalancing' process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet